Актуальні проблеми формування здоров’я дітей, народжених недоношеними. Літературний огляд. Частина 2 - Боярська, Людмила Миколаївна; Великанова, Тетяна Василівна; Boyarska, L. M.; Velykanova, T. V.; Боярская, Л. Н.; Великанова, Т. В. (ВДНЗ «Українська медична стоматологічна академія», 2015)
У статті надано огляд сучасної літератури з питань ролі батьків у фізичному та психомоторному розвитку дітей, які народилися з дуже низькою (ДНÌТ) та екстремально низькою масою тіла (ЕНÌТ). В цьому напрямку проаналізовані існуючі практики, спрямовані на оптимізацію розвитку цих дітей, визначені перспективи подальших досліджень. Враховуючи те, що в Україні на теперішній час немає доступних для педіатрів, сімейних лікарів, поліклінічних неврологів спеціальних уніфікованих алгоритмів допомоги таким сім’ям, розробка будь-якого аспекту цього питання буде надзвичайно важливою та затребуваною. The health status and quality of life of preterm infants with DNMT and ENMT at birth depends largely on effective solutions rehabilitation programs where significant role played by the family. Currently, this issue requires further study and improvement. The aim of research. Analysis of modern scientific literature on rehabilitation of premature infants Results. After birth, preterm mothers experiencing psychological shock and disappointment that can form in the reaction of parents’ emotional rejection. “Later, anxiety leads to behavioral disorders and difficulties of social adaptation of the child. Therefore, the quality of the morning (0-6 months of life) mother-child relationship is the first of the factors that can lead to exacerbation or mitigate the potential negative effects of premature birth on child development. Of early and ongoing counseling reduces the level of stress in all members of the family and leads to complete their recovery in child reaches 2 years. Therefore, the effectiveness of early rehabilitation programs aimed at correction of psychomotor development and a high level of social adaptation of a premature baby, it depends on the active participation of parents. Formed and secured in a hospital relationships at home contribute to the proper development of the child on the one hand and on the other – reduce parental stress and parental depression and increases self-esteem. In addressing the issue of long-term effects of early rehabilitation programs preterm significant role played by social pediatrics – interdisciplinary field whose mission is the living space of a child in a society based on the state of her health. The concept of social pediatrics involves creating opportunities for the development of the child is still missing activities that help acquire skills in accordance with its capabilities. This process with experts of various professions: psychologists, therapists, teachers and social workers. They assess the extent of the problems of the individual patient, develop and implement customized solutions. It is important that the process of overcoming the disease and its consequences are actively involved family members, because outside of the center, which assists in the outpatient mode, the main role in the rehabilitation and social adaptation sick child do her parents and micro-environment. In Ukraine, due to the increasing number of children born prematurely and needing the age of specialized rehabilitation and remedial care, social pediatrics is highly in demand. Particularly important is the creation of new programs of rehabilitation and habilitation of children. In 1998 the Ministry of Health of Ukraine was adopted and implemented in the work of the Ukrainian Medical Center for medical and social rehabilitation of children with central nervous system lesions model “Tandem-Partnership”, “child-family specialist. ” The essence of the model is the harmonious combination of medical and socio-economic aspects of rehabilitation with obligatory participation of parents as full participants in the rehabilitation process. The model “Tandem-Partnership” implemented substantive provisions of social pediatrics. However, this work was done on the bases of large clinics and centers (Kyiv, Truskavets), and for the dissemination of such programs, you must create social pediatrics centers in each region. Development and implementation of individual rehabilitation programs should be accompanied by a dynamic assessment of their effectiveness in meeting the needs of the patient using objective criteria, such as survey of parents rating the quality of life of their child. Conclusion. Based on the foregoing and given the fact that Ukraine is at present not available for pediatricians, family physicians, neurologists specialized outpatient standardized algorithms help such families, and the development of any aspect of this issue is very important and popular.
Актуальные проблемы формирования здоровья детей, рожденных недоношенными. Литературный обзор. Часть 2
Actual problems of formation of health of infants born prematurely. Literature review. Part 2
Keywords: недоношені діти; народжені з дуже низькою та екстремально низькою масою тіла; роль батьків; соціальна педіатрія; тандем-партнерство; premature infants born with very low (DNMT) and extreme low birth weight (ENMT); the role of parents; social pediatrics; tandem partnership; недоношенные дети; рожденные с очень низкой и экстремально низкой массой тела; роль родителей; социальная педиатрия; тандем-партнерство